2021
DOI: 10.3389/fncel.2021.750373
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Microglial Activation and SARS-CoV-2 Receptor Expression Induced by Chronic Unpredictable Stress

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has generated a lot of stress and anxiety among not only infected patients but also the general population across the globe, which disturbs cerebral immune homeostasis and potentially exacerbates the SARS-CoV-2 virus-induced neuroinflammation, especially among people susceptible to neuropsychiatric disorders. Here, we used a chronic unpredictable mild stress (CUMS) mouse model to study its effects on glia-mediated neuroinflammation and expression of SARS-CoV2 vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…It is noteworthy that MCHII + -microglia were decreased in mAb102 group, indicating a neuroprotective role of this subgroup of microglia. Aligned with this, our recent study found that CUS increased hippocampal MCHII + -microglia in female mice that were more resilient to stress-induced anxiety as compared to male mice ( 32 ). Additionally, PLXNB2 is a functional receptor for ANG that promotes angiogenesis and neurite outgrowth ( 49 ), sequelae that microglia closely monitor as well ( 50 ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It is noteworthy that MCHII + -microglia were decreased in mAb102 group, indicating a neuroprotective role of this subgroup of microglia. Aligned with this, our recent study found that CUS increased hippocampal MCHII + -microglia in female mice that were more resilient to stress-induced anxiety as compared to male mice ( 32 ). Additionally, PLXNB2 is a functional receptor for ANG that promotes angiogenesis and neurite outgrowth ( 49 ), sequelae that microglia closely monitor as well ( 50 ).…”
Section: Discussionsupporting
confidence: 61%
“…Mice ( n =7+7 in both CUS and microinjection) were sacrificed with CO 2 . Tissues were gently homogenized through 70µm cell strainers (#352350, BD Biosciences) on ice as we described previously ( 24 , 32 ). Homogenates were blocked in PBS+10% rat serum for 1h with gentle rotation at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…OFT was used to assess anxiety and locomotion was performed according to [34]. Mice were placed in an experimental room for about 1 h before starting the experiment for their habituation.…”
Section: Open Field Test (Oft)mentioning
confidence: 99%
“…After a week (wk) of transfer adaptation, mice were randomly assigned into 4 groups: Control (Ctr)-Vehicle (Veh) (n = 9), CUS-Veh (n = 9), Ctr-CSF1Ri (n = 10), and CUS-CSF1Ri (n = 10), and subject to CUS/Ctr and CSF1Ri (PLX3397)/Veh treatments. CUS procedure was previously described [42]. PLX3397 (HY-16749/CS-4256, MedChemExpress) was dissolved in DMSO (D8418, Sigma-Aldrich) and freshly diluted with corn oil (#8267, Sigma-Aldrich).…”
Section: Mri Acquisition and Processingmentioning
confidence: 99%